Malpractice Litigation in Hand Surgery: A Comprehensive Nationwide Analysis. (November 2022) - Umpierrez, Erica; Ohliger, Erin; Scollan, Joseph P.; Styron, Joseph F.
Background: The circumstances surrounding claims against hand surgeons have not been elucidated in the literature. The purpose of this study was to analyze trends in malpractice litigation regarding hand surgery through a nationwide legal database. Methods: The Westlaw legal research database was queried for verdicts and settlements between 1985 and 2017 for hand surgery–related malpractice cases. Cases were included if the hand surgeon was sued for malpractice. Procedure type and complications and/or adverse events that resulted in litigation were recorded. Patient characteristics, state, date of case, case outcomes, and indemnity payment were also noted. All dollar amounts were adjusted to 2017 values using the Consumer Price Index. Results: In all, 171 cases (35 states) were included. The most frequently litigated surgeries were carpal tunnel releases followed by fracture treatment. Nerve injury was the predominant cause of litigation. The median nerve was predominantly injured, followed by the ulnar and radial nerves. In fracture surgery, malunion was the predominant cause, followed by weakness, nerve injury, and infection. In total, 72.5% of cases yielded verdicts in favor of the defense, 21.6% favored the plaintiff, and 5.9% were settled. Indemnity varied between $7800 and $8.99 million, averaging $570, 397 for cases when the jury ruled in favor of the plaintiffs. Settled cases averaged $1, 140, 527. Conclusions: Malpractice litigation has substantial financial implications on surgeons and the health care system. Litigation arises most commonly from routine procedures (carpal tunnel release and fracture fixation) rather than complex surgical cases, potentially due to the high variability in operating surgeon subspecialization, with discrepant training.